Generating and compressing images from a large volume of discrete datasets using GANs along with different compression techniques and studying the results - Sajid, Mayeen Abedin; Jisan, Md. Tanvir Mahtab; Reza, Syeda Nowrin; Jueb, Ashraf Mufidul Islam; Meem, Tahmin Khandaker (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.